Strategi Guru Pendidikan Agama Islam Dalam Mengatasi Kesulitan Belajar terhadap Peserta Didik kelas VIII.1 SMP Negeri 11 Makassar: penelitian Kualitatif - marifah, Nur; Akhmad Syahid; Muh. Aidil Sudarmono R; Andi Bunyamin; Mustamin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The student examines the learning difficulities of student in class VIII.1 SMP Negeri 11 Makassar in the subject of Islamic Education (PAI). The objective of this study is to determine the strategies used by PAI teachers to overcome learning difficulties of students. This study uses a qualitative method with a descriptive approach. Data were collected through interviews with PAI teachers and direct observation in the classroom. The results showed that PAI teachers use various strategies to overcome learning difficulties, including: (1) Personal approach: PAI teachers use a personal approach to understand students' needs and learning difficulties. (2) Varied learning methods: PAI teachers use varied learning methods to increase students' interest and motivation. (3) - Interesting learning media: PAI teachers use interesting learning media to help students understand difficult concepts.